Analysis of demand-supply interaction and inventory build-up strategies for products with short life cycles. (1st January 2013) - Solis, Adriano O.; Pan, Rong; Paul, Bixler; Nicoletti, Letizia
Revenues and profits from short life cycle products will depend upon careful formulation and execution of production plans in response to demands in the marketplace. This research contributes to the development of the production and inventory build-up strategies for short life cycle products under different demand-supply scenarios. A modified Bass diffusion model is used to characterise the product demand pattern with consideration of demand-sales interaction. We develop cost models based on production costs, inventory carrying costs, backlog costs, and cost of lost sales for a number of different production scenarios. The optimal production rate is obtained by minimising the total cost. We also investigate the benefit of an initial build-up of inventory before the product's sales period starts.